Emergency Rhetoric in the US Congress: Debating the National Emergencies Act of 1976 - Kronlund, Anna (Res Publica. Revista de Historia de las Ideas Políticas, 2015)
From the Constitutional Convention onwards the question of emergency powers has been central to political discussions in the United States. The debates on the National Emergencies Act of 1976 (“NEA”) can be seen, however, as specifically relevant to the conception of the state of emergency in US constitutional politics. The law placed the process of declaring, executing, and terminating a state of emergency on a statutory footing and established new procedures for dealing with further emergencies. The paper examines, through the debates, the question of to what extent president’s war/emergency powers are contingent on Congress exploiting its own constitutional powers. The problematic of dealing with emergency powers through the framework of a statutory delegation of power is also addressed.